Activated Nrf2 impairs liver regeneration in mice by activation of genes involved in cell‐cycle control and apoptosis. Issue 2 (18th June 2014) - Köhler, Ulrike A.; Kurinna, Svitlana; Schwitter, Dominik; Marti, Andrea; Schäfer, Matthias; Hellerbrand, Claus; Speicher, Tobias; Werner, Sabine
<x xml:space="preserve">Abstract</x> The nuclear factor erythroid‐derived 2, like 2 (Nrf2) transcription factor is a key regulator of the antioxidant defense system, and pharmacological activation of Nrf2 is a promising strategy for prevention of toxin‐induced liver damage. However, the consequences of Nrf2 activation on liver regeneration (LR) have not been determined. To address this question, we generated mice expressing a constitutively active Nrf2 (caNrf2) mutant in hepatocytes. Expression of the transgene did not affect liver homeostasis. Surprisingly, however, there was no beneficial effect of Nrf2 activation on CCl4‐induced liver injury and fibrosis. Most important, LR after partial hepatectomy was impaired in caNrf2‐transgenic mice as a result of delayed hepatocyte proliferation and enhanced apoptosis of these cells after liver injury. Mechanistically, this involved up‐regulation of the cyclin‐dependent kinase inhibitor p15 and the proapoptotic protein Bcl2l11 (Bim). Using chromatin immunoprecipitation, we show that the p15 and Bcl2l11 genes are direct targets of Nrf2, which are activated under hyperproliferative conditions in the liver. Conclusion: Activated Nrf2 delays proliferation and induces apoptosis of hepatocytes in the regenerating liver. These negative effects of Nrf2 activation on LR should be considered when Nrf2‐activating compounds are used for prevention of liver damage. (Hepatology 2014;60:670–678)